Insān wa zamīn - Mūsawī, Maḥbūba (Intišārāt-i Murwārīd, 2023)
Nature in literature – History and criticism. ; Environmental literature – History and criticism. ; Environmental protection – Fiction. ; Nature in literature
Keywords: Persisch; Literatur; Umwelt; Mensch; Erde